Correlates of job satisfaction among teachers of students with hearing impairment in Ibadan, Oyo state, Nigeria (2016)
This study investigated the relationship among gender, marital status, self efficacy, incentives and job satisfaction among teachers of students with hearing impairment in Ibadan, Oyo State, Nigeria. This is against the background that teachers commitment and productivity will depend on how satisfied they are in terms of personal, psychological and environmental factors. The sample consisted of 60 secondary school teachers of students with hearing impairment in Ibadan (Male = 31, female = 29). The respondents were selected using purposive sampling technique. Data were collected using Teachers of students with hearing impairment job satisfaction Questionnaire (r=0.86). Results showed that Gender (r-271) and self efficacy (r=.263) had significant relationship with job satisfaction among teachers of students with hearing impairment. While marital status, incentives and years of teaching experience did not. The independent variables (gender, self efficacy marital status, incentives and years of teaching experience jointly contributed to job satisfaction among teachers of students with hearing impairment (Adj. R2=0.178). This means that 17.8% of the variance in job satisfaction is accounted for by the independent variables. The relative contributions of the independent variables to the dependent variable in order of magnitude showed that: Gender ((3=0.559), self efficacy ((3=0.417), Marital status ((3=0.245) and years of teaching experience (3=0.125). It is recommended that the government should ensure that teachers of students with hearing impairment’s conditions of service are improved, so that they could be job satisfied. This will influence their productivity and performance.